Nursing and planetary health: A discussion article - Salima Meherali; Saba Nisa; Yared Asmare Aynalem; Zohra S Lassi (Women's Health)
This discussion article discusses the integration of planetary health into nursing practice and education, highlighting the transformative potential of this approach in improving global health outcomes. Planetary health emphasizes the interdependence between human health and the health of our planet’s ecosystems, advocating for a sustainable approach to healthcare. This article explores how nursing practice can incorporate planetary health principles to address environmental determinants of health and promote sustainable practices. It also discusses the role of nursing education in preparing future practitioners to understand and act on the links between environmental sustainability and health. By aligning nursing education with planetary health objectives and fostering leadership in this area, the nursing profession can contribute significantly to addressing global health challenges, advocating for systemic changes, and implementing practices that protect both human and environmental health.